Evaluation of the Antimicrobial Activity of Alkaloid Extracts of Four Papaver Species - Ahmad Ismaili *; Seyyed Mohsen Sohrabi; Mojgan Azadpour; Rouhollah Heydari; Marzieh Rashidipour (Lorestan University of Medical Sciences, 2018)
Background and Aim: The use of bioactive compounds of medicinal plants in prevention, control and treatment of human diseases has a long history. Most of plant bioactive compounds have highly complex chemical structures, and their chemical syntheses are often uneconomical. Moreover, their production is still dependent on plants. Plants of Papaveraceae family contain a variety of bioactive compounds that have many uses in traditional and modern medicine. In the present study, we evaluated the antimicrobial activity of alkaloid extracts of four plant species of Papaveraceae family against some human pathogens. Materials and Methods: Crude alkaloid compounds of Papaver macrostomum, Roemeria refracta, Papaver somniferum and Glaucium grandiflorum plants were extracted using cain method.  The antimicrobial activity of plant alkaloid extracts against Pseudomonas aeroginosa PTCC 1310, Listeria monocytogenes PTCC 1297, Staphylococcus aureus PTCC 1189, Klebsiella pneumoniae PTCC 1290 and Candida albicans PTCC 5027 pathogens were assessed using agar diffusion method. Results: The results of this study indicated that the alkaloid extracts of tested plants were effective against fungal and bacterial pathogens. All plant alkaloid extracts exhibited more inhibitory effect against fungal pathogen than the bacterial pathogens. Comparison of MIC and MBC values for bacterial pathogens revealed that all plant alkaloid extracts showed more inhibitory effects against the gram-positive bacteria than gram-negative bacterial pathogens. The results also showed that the alkaloid extracts of R. refracta have stronger inhibitory effect against fungal and bacterial pathogens compared with other plants. Conclusion: The antimicrobial compounds present in the plant species of Papaveraceae family are suitable candidates to produce new antibiotics. The results of this study demonstrated that antimicrobial compound in R. refracta plant could be used in the treatment of infectious diseases caused by C. albicans and S. aureus pathogens.